Lack of cool, not warm, extremes distinguishes late 20th Century climate in 979-year Tasmanian summer temperature reconstruction. (15th March 2018) - Allen, K J; Cook, E R; Evans, R; Francey, R; Buckley, B M; Palmer, J G; Peterson, M J; Baker, P J
Abstract: Very few annually resolved millennial-length temperature reconstructions exist for the Southern Hemisphere. Here we present four 979-year reconstructions for southeastern Australia for the austral summer months of December–February. Two of the reconstructions are based on the Australian Water Availability Project dataset and two on the Berkeley Earth Surface Temperature dataset. For each climate data set, one reconstruction is based solely on Lagarostrobos franklinii (restricted reconstructions) while the other is based on multiple Tasmanian conifer species (unrestricted reconstructions). Each reconstruction calibrates 50−60% of the variance in the temperature datasets depending on the number of tree-ring records available for the reconstruction. We found little difference in the temporal variability of the reconstructions, although extremes are amplified in the restricted reconstructions relative to the unrestricted reconstructions. The reconstructions highlight the occurrence of numerous individual years, especially in the 15th−17th Centuries, for which temperatures were comparable with those of the late 20th Century. The 1950−1999 period, however, stands out as the warmest 50-year period on average for the past 979 years, with a sustained shift away from relatively low mean temperatures, the length of which is unique in the 979-year record. The reconstructions are strongly and positively related to temperatures across the southeast of the Australian continent, negatively related to temperatures in the north and northeast of the continent, and uncorrelated with temperatures in the west. The lack of a strong relationship with temperatures across the continent highlights the necessity of a sub-regional focus for Australasian temperature reconstructions.